2021
DOI: 10.1101/2021.10.07.21264679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severity of thermal burn injury is associated with systemic neutrophil activation

Abstract: Objectives Burn injuries elicit a unique and dynamic stress response which can lead to burn injury progression. Though neutrophils represent crucial players in the burn-induced immunological events, the dynamic secretion pattern and systemic levels of neutrophil-derived factors have not been investigated in detail so far. Methods Serum levels of neutrophil elastase (NE), myeloperoxidase (MPO), citrullinated histone H3 (CitH3), and complement factor C3a were quantified in burn victims over 4 weeks post injury. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Moreover, in the current research, WBC was suggested to form an independent risk factor for determining the severity of SII, ARDS development in patients with SII and SII mortality. Consistent with our previous study that the severity of thermal burn injury is associated with WBC activation, WBC and neutrophil counts were significantly increased on admission day (40). Compared with the other indicators in severity of SII group, the highest AUC and sensitivity were 0.774 and 75.0%, respectively.…”
Section: Univariate Logistic Regression Multivariate Logistic Regressionsupporting
confidence: 90%
“…Moreover, in the current research, WBC was suggested to form an independent risk factor for determining the severity of SII, ARDS development in patients with SII and SII mortality. Consistent with our previous study that the severity of thermal burn injury is associated with WBC activation, WBC and neutrophil counts were significantly increased on admission day (40). Compared with the other indicators in severity of SII group, the highest AUC and sensitivity were 0.774 and 75.0%, respectively.…”
Section: Univariate Logistic Regression Multivariate Logistic Regressionsupporting
confidence: 90%
“…We also found increased CitH3 and NE concentrations following severe trauma, whereas these differences were not stated as signi cant. Interestingly, measured serum levels of MPO, CitH3, and NE were lower than those in patients suffering from burn injuries 22 . These results indicate a lower induction of NETosis in polytraumatized patients compared with burn injury patients.…”
Section: Discussionmentioning
confidence: 77%
“…Previously, we were able to demonstrate systemic neutrophil activation after burn injury 22 . This is in accord with other studies reporting a role for neutrophils and NETs in burn injury 27 ,, ,28 ,critically ill patients 21 , sepsis 29 , and lung injury 30 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is worth noting that we detected different expression of the same gene in the blood and skin at different burn times. In the process of severe burn, there are a series of immune reactions such as inflammation (20). This shows that the same reaction mechanism is present in different burn times.…”
mentioning
confidence: 96%